Desiccant coated heat exchanger and its applications. (October 2021) - Zhao, L.H.; Wang, R.Z.; Ge, T.S.
Abstract: Desiccant coated heat exchanger (DCHE) has shown great potential for dehumidification in vapor compression cooling systems and has been widely concerned in the research field of air conditioning, as well as heat and mass transfer in recent years. This paper is aimed at providing fundamental knowledge and research progresses on DCHE for dehumidification and cooling. Initially, DCHE dehumidification is chosen as the research object in this review due to its superiority of the principle by comparing with other two typical dehumidification processes, which are condensation dehumidification and rotary-wheel dehumidification. Then, intermittent dehumidification and continuous dehumidification as two operation modes of DCHE are compared. Finally, the variation characteristics of temperature and humidity during operation are discussed. The current studies of DCHE are reviewed from four aspects, including desiccant coating, cooling source, regeneration heating source and basic heat exchanger. The performance analysis of DCHE is then conducted, according to the different effects of above aspects acting on dehumidification performance, cooling performance and energy efficiency of DCHE. The ongoing researches indicate that the rational construction of DCHE is an effective way to achieve its multi-objective performance optimization. The significant progress of DCHE lays the foundation for applications on other fields. However, further research is required in the field of the selection of desiccant coatings and the structure of heat exchangers to broaden its application market.